THE DIAGNOSTIC EFFICACY OF SPECT/CT IN DETECTION OF BONE METASTASES IN PATIENTS WITH BREAST AND PROSTATE CANCER - Е. А. Glushkov; A. G. Kislichenko; М. S. Ramazanova (Сибирский онкологический журнал, 2016)
The present study was undertaken to evaluate the benefit of single photon emission computed tomography/ computed tomography (SPECT/CT) over SPECT alone, osteoscintigraphy (OSG), CT and conventional X-ray for the detection of bone metastasis in patients with breast cancer (BC) and prostate cancer (PC). 72 BC patients and 17 PC patients at high risk of developing bone metastasis were examined by (SPECT/ CT), SPECT,OSG,CTand conventional X-ray. Bone metastases were detected in 33 (37.1 %) patients. It was found that the diagnostic efficacy (sensitivity, specificity and accuracy) of SPECT/CT was significantly superior to that of the other types of imaging modalities in detection of bone metastases from BC. In addition, the combination of SPECT with CT resulted in a change in SPECT and CT findings on skeletal metastasis in 5 (6 %) and 11 (12 %) cases, respectively.